Sports Management Structure of the The German Democratic Republic (GDR) and State Plan 14.25 - UYAR , Hamza; ÇOLAKOĞLU , Tekin; YETİM , A.Azmi; UYAR , Yalçın (Sportif Bakış: Spor ve Eğitim Bilimleri Dergisi, 2023)
After the Second World War, East Germany achieved great success in sports in a short time despite its political and geographical disadvantages. East Germany was imitating the strategies of the Soviet Union. For this reason, they decided that the best way to show the success of the sports system as the success of its own ideological system and to introduce itself to the world public is sports. For this reason, they have established all sports institutions in line with this purpose and have shaped the sports management structure accordingly. The decision of the International Olympic Committee to recognize the East Germany Olympic Committee in 1965 and it was the most important point of the country's sport. After that, East Germany took the first place in the medal ranking in all Olympic Games it participated in summer and winter sports. The achievements of East Germany attracted great attention around the world. The sports management structure and organization that provided these achievements has been a matter of curiosity. However, with a population of only 17 million, these achievements shortly after its establishment have raised serious questions. With the unification of East and West Germany in 1990, some documents came to light. These documents showed that questions were not unjustified. These documents were labeled "Top Secret" by the East Germany. A project called “State Plan 14.25” of East Germany was implemented. They brought together scientists who were experts in many fields of science. Thus, it has been revealed that they research on athlete performance and doping. In the statements of the East German athletes of the period, which were also recorded in the court minutes, it was mentioned that this plan was not only about research, but that drugs were produced for the performance enhancement of the athletes within the scope of this plan. It was determined that these drugs were tested on the athletes and that the athletes who refused to use the drugs were exposed to threats and exclusion, and many violations were committed. The purpose of this study is to examine the sports management structure of the Republic of East Germany (GDR) and the practices behind its sporting achievements in accordance with the State Plan 14.25.